Analysis of Teacher Effectiveness at ATSU Pedagogical Faculty - Moralishvili, Sophio; Adeishvili, Vladimer (European Journal of Social Science Education and Research, 2021)
The aim of the paper is to find out if university teacher effectiveness is connected to the school-related experience. It also gives a brief overview of the related literature to the teacher effectiveness and tries to reveal the major qualities of effective teaching. Generally, teaching is a multidimensional process comprising a number of separable dimensions or instructor attributes, which sometimes are difficult to evaluate. The study was carried out to find out if university teacher effectiveness is connected to the school-related experience. We used primarily interviews, which were designed, as far as possible, to allow the students to talk freely about their University professors, using the terms and expressions of their own. Six university professors were selected; three of them did not have any school-related experience and three had experience of working at schools for different periods. The paper concludes that school-related experience is not a success factor in teacher effectiveness.
Keywords: teacher effectiveness, school-related experience, theoretical knowledge, practical teaching